Secrets typed in blood : a Pentecost and Parker mystery - Spotswood, Stephen (Spotswood, Stephen. Pentecost and Parker mystery, 2022)
"In the newest entry into the Nero Award-winning Parker & Pentecost Mystery series ("my new favorite sleuthing duo"-- Sarah Weinman, The New York Times Book Review), Lillian and Will are hot on the trail of a serial killer whose murders are stranger than fiction. New York City, 1947: For years, Holly Quick has made a good living off of murder, filling up the pages of pulp detective magazines with gruesome tales of revenge. Now someone is bringing her stories to life and leaving a trail of blood-soaked bodies behind. With the threat of another murder looming, and reluctant to go to the police, Holly turns to the best crime-solving duo in or out of the pulps, Willowjean "Will" Parker and her boss, famed detective Lillian Pentecost. The pair are handed the seemingly-impossible task of investigating three murders at once without tipping off the cops or the press that the crimes are connected. A tall order made even more difficult by the fact that Will is already signed up to spend her daylight hours undercover as a guileless secretary in the hopes of digging up a lead on an old adversary, Dr. Olivia Waterhouse. But even if Will is stuck in pencil skirts and sensible shoes, she's not about to let her boss have all the fun. Soon she's diving into an underground world of people obsessed with murder and the men and women who commit them. Can the killer be found in the Black Museum Club, run by a philanthropist whose collection of grim murder memorabilia may not be enough to satisfy his lust for the homicidal? Or is it Holly Quick's pair of editors, who read about murder all day, but clearly aren't telling the full story? With victims seemingly chosen at random and a murderer who thrives on spectacle, the case has the great Lillian Pentecost questioning her methods. But whatever she does, she'd better do it fast. Holly Quick has a secret, too and it's about to bring death right to Pentecost and Parker's doorstep"--